Lousy sex: creating self in an infectious world - Callahan, Gerald N., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2013)
In Lousy Sex Gerald Callahan explores the science of self, illustrating the immune system's role in forming individual identity. Blending the scientific essay with deeply personal narratives, these poignant and enlightening stories use microbiology and immunology to explore a new way to answer the question, who am I? Self" has many definitions. Science has demonstrated that 90 percent of the cells in our bodies are bacteria--we are in many respects more non-self than self. In Lousy Sex, Callahan considers this microbio-neuro perspective on human identity together with the soulful, social perception of self, drawing on both art and science to fully illuminate this relationship. In his stories about where we came from and who we are, Callahan uses autobiographical episodes to illustrate his scientific points. Through stories about the sex lives of wood lice, the biological advantages of eating dirt, the question of immortality, the relationship between syphilis and the musical genius of Beethoven, and more, this book creates another way, a chimeric way, of seeing ourselves. The general reader with an interest in science will find Lousy Sex fascinating.--Provided by publisher.
Keywords: Self; Identity (Psychology); Biological psychiatry; Psychoanalysis